(3GdPjd hGdUdI dcJGH GdJcedIs - (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf , J (B650 (3g` s; (3GdLhgQj , ESeGYjd Hf MeGO GdLhgQj, CHh fUQ GdaGQGHj,J (B393 (3g` s
(3ChdgG (B:s
(3gPg MGTjI Pjd GdUMGM ai GddZI ef JCdjai GdeSei HGdJcedI hUdJg s
(3GdJcedI hGdUdI Pjdg GdeDda Ydi cJGH JGL GddZI hUMGM GdYQHjI ddLhgQis
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
Keywords: (3GddZIs